1986
DOI: 10.1002/cne.902530106
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical study on the development of serotoninergic neurons in the chick: I. Distribution of cell bodies and fibers in the brain

Abstract: The ontogenetic development of the serotoninergic system in the embryonic as well as in posthatching chick brain was studied with an indirect immunohistochemical technique with the aid of a specific antibody to serotonin (5-hydroxytryptamine). By embryonic day 4, rostral and caudal groups of serotonin-immunoreactive cell populations appeared in the mesencephalon and rostral and caudal rhombencephalon. At this stage, the rostral group had a considerable number of labelled cells that sent axons toward more rostr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 33 publications
1
33
0
Order By: Relevance
“…The topographic and functional organization of the serotonergic system has been highly conserved from reptiles to birds and mammals (Dubé & Parent, 1981;Parent, 1981;Parent et al, 1981;Duchala et al, 1984;Sako et al, 1986;Cozzi et al, 1991;Challet et al, 1996). In fact, the ubiquitous phylogenetic distribution of the serotonergic system has raised the hypothesis that this system represents a neural substrate integrating similar mechanisms that remain intact throughout the vertebrate kingdom (Parent, 1981).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The topographic and functional organization of the serotonergic system has been highly conserved from reptiles to birds and mammals (Dubé & Parent, 1981;Parent, 1981;Parent et al, 1981;Duchala et al, 1984;Sako et al, 1986;Cozzi et al, 1991;Challet et al, 1996). In fact, the ubiquitous phylogenetic distribution of the serotonergic system has raised the hypothesis that this system represents a neural substrate integrating similar mechanisms that remain intact throughout the vertebrate kingdom (Parent, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…In birds, a dense serotonergic-fiber distribution has been identified in diencephalic regions known to be involved in controlling feeding behavior (Parent, 1981;Duchala et al, 1984;Sako et al, 1986;Challet et al, 1996). However, studies regarding the role of serotonergic pathways in the control of food intake in birds are rare (Rosebrough, 1996;Thomaz et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The serotoninergic innervation of the nBOR was previously described in the chicken, and it was shown to develop mainly in the posthatching period (Sako et al, 1986). The presence of 5-HT terminals in the AOS nuclei was also reported in the lizard (Smeets & Steinbusch, 1988;Wolters et al, 1985).…”
Section: Classical Transmitters and Receptorsmentioning
confidence: 73%
“…Several recent studies have indicated the possible presence of other transmitter/peptide/receptor molecules in the AOS nuclei; e.g. an extensive AOS serotoninergic innervation was described in the chicken (Sako et al, 1986) and the lizard (Smeets & Steinbusch, 1988;Wolters et al, 1985), and binding sites for both neurotensin (Brauth et al, 1986) and opioids (Atweh & Kuhar, 1977;Atweh et al, 1978;Reiner et al, 1989) were shown to be present in AOS nuclei.…”
Section: Introductionmentioning
confidence: 99%
“…The topographic and functional organization of the serotonergic system in birds maintained homologies with reptiles and mammals (Dubé & Parent, 1981;Parent, 1981;Parent et al, 1981;Duchala et al, 1984;Sako et al, 1986;Cozzi et al, 1991;Challet et al, 1996;Gruss & Braun, 1997). However, studies about the participation of serotonin receptors in the feeding behavior of quails (Coturnix japonica) are absent from the literature, although receptors for serotonin have been identified in bird brains (Gleeson et al, 1992;Saadoun & Cabrera, 2002).…”
Section: Introductionmentioning
confidence: 99%